THE EFFECT OF FLASH SALE AND FREE SHIPPING PROMOS ON PURCHASE DECISIONS ON E-COMMERCE SHOPEE (Case Study of STIE Bina Karya Tebing Tinggi Students) - CAHYADI, LUKIETO (International Conference on Health Science, Green Economics, Educational Review and Technology, 2020)
The e-commerce business is growing and developing rapidly in Indonesia, the high interest in online shopping in the community has made a lot of new e-commerce pop up in Indonesia. One of the largest e-commerce providers in Indonesia is Shopee. Flash sale programs and free shipping promotions make Shopee one of the most popular online platforms in Indonesia. This study aims to analyze how the effect of flash sales and free shipping promotions on purchasing decisions of e-commerce Shopee (a case study on STIE Bina Karya Tebing Tinggi student). This type of research is quantitative research with an associative approach. Sampling used a purposive sampling technique and used 65 respondents as samples. The primary data used in this study was obtained by distributing questionnaires via Google form, while the secondary data was obtained through a literature study. The data analysis method used the validity test, reliability test, classical assumption test, multiple linear regression test, and hypothesis test. The results of the research conducted showed that the flash sale variable (X1) did not significantly influence purchasing decisions. Meanwhile, the variable free shipping promo (X2) has a significant effect on purchasing decisions, however, the flash sale and free shipping promo variables simultaneously (simultaneously) affect purchasing decisions (Y). The coefficient of determination test shows that there is a fairly close relationship between flash sales and free shipping promotions on purchasing decisions with an R-value of 0.836. Through the adjusted R square value, it is also known that the flash sale variable and free shipping promo contributed 69% to the purchasing decision variable,